Community learning centers program as an educational tool for community literacy development in the Islamic Republic of Iran: community of Golshan as a case study - Zolfaghari, Akbar; Sabran, Mohammad Shatar; Zolfaghari, Azam (Canadian Center of Science and Education, 2009)
Literacy plays an important role in Community Development (CD). Without literacy, people have difficulties improving their quality of life. Iran is no exception. Since the Islamic Revolution, the government of Iran has allocated great efforts and budgets on the literacy development to improve the quality of life. Following these efforts, the government has implemented various literacy programs. One of the major literacy programs that have been implemented for this purpose is the Community Learning Centers Program (CLCP). CLCP is the newest literacy program that has been implemented to develop literacy in order to improve the quality of life. CLCP has been emerged as a result of shortcomings of the previous literacy programs to solve the problem of illiteracy among people in the country. So far, the government of Iran has implemented 3517 CLCP into 3517 both rural and urban communities throughout the country. One of these rural communities is community of Golshan. Therefore, the main objective of this paper is to examine the role of CLCP in Community Literacy Development (CLD) in the community.